The “water machine” of Bengal: a data-driven and policy-supported strategic use of aquifers for irrigation is needed to maximize their benefits - Mukherji, Aditi (American Association for the Advancement of Science, 2022)
For decades, millions of farmers in Bangladesh have been capturing more water than even the world’s largest dams. They did so simply by irrigating intensively in the summer dry season using water from shallow wells. The ability to use groundwater to irrigate rice paddies during the dry seasons (January to May) helped Bangladesh become food self-sufficient by the 1990s, which was no small feat for one of the most densely populated countries in the world. Researchers proposed that lowering of the groundwater table as a result of intensive irrigation practices in the dry season created conditions for recharge from monsoon rains (June to September), which then replenishes the groundwater (1). On page 1315 of this issue, Shamsudduha et al. (2) present a quantitative analysis of this depletion-replenish process and show that this recharge has indeed been happening at a large scale, in a process they call the Bengal Water Machine (BWM).